Utilization of Bamboo Powder in The Production of Non-Asbestos Brake Pads: Computational Bibliometric Literature Review Analysis and Experiments to Support Sustainable Development Goals (SDGs) - Asep Bayu Dani Nandiyanto; Aisha Nadhira Syazwany; Karina Nur Syarafah; Themy Sabri Syuhada; Risti Ragadhita; Erna Piantari; Obie Farobie; Muhammad Roil Bilad (Automotive Experiences, 2024)
This study aims to develop asbestos-free and environmentally friendly brake pads using apus bamboo powder (Gigantochloa apus). In the experiments, bamboo powder, resin, and catalyst were used as the raw materials and varied to ensure the quality of the prepared brake pads. To analyze the performance of brake pads, the fabricated brake pads are subjected to physicochemical tests (such as microscopic tests and functional group analysis) and mechanical tests (such as puncture tests, compression tests, and friction tests). The research results showed that adjusting the composition of the raw materials allowed a change in the performance of the brake pad, including porosity, morphological structure, and mechanical properties. Indeed, the condition of the low porosity on the inside of the brake pad strategically optimizes the compression strength of the material, making this design ideal for applications that require high resistance to compression loads. This study shows the possibility of apus bamboo powder as an alternative to asbestos in the production of non-asbestos brake pads, offering a safer and environmentally friendly solution as well as giving ideas for supporting current issues in the sustainable development goals (SDGs).